Speciality rubber latex foam: Foamability study and fabrication process - Ramli, R; Chai, A.B; Ho, J.H; Kamaruddin, S; Mohd Rasdi, F.R; De Focatis, D.S.A (Rubber Chemistry and Technology, 95(3): 492-513., 2022)
Specialty natural rubber (SpNR) latex, namely, deproteinized natural rubber (DPNR) latex and epoxidized natural rubber (ENR) latex, has been produced to meet specific product's requirements. However, SpNR is normally used in the form of block rubber to manufacture dry rubber products such as tires and automotive parts. The applications of SpNR latex into latex foam products will be diversified. Findings indicate that foamability of SpNR latex is lower compared to normal latex (LATZ) but shows longer stability time after foamed. Findings also indicate that foam collapse and foam coagulate are two main challenges in the fabrication process of SpNR latex foam. Despite these challenges, SpNR latex foam can be fabricated at different density levels. During the foaming process, additional foaming agent is required to fabricate a SpNR latex foam, which is different from fabricating a normal NR latex foam, especially at low latex foam density. Consequently, a higher level of sodium silicofluoride, used as the gelling agent, is required to set the cell structure of the foam. Findings also indicate that foam density influenced the gelling time and volume shrinkage of the SpNR latex foam. An ideal compounding, foaming, and gelling formulation to fabricate SpNR latex foam via Dunlop batch foaming process has been developed. Morphological study showed that all latex foams are open-cell structure, with lower density foam exhibiting higher porosity and mean pore size. Comparison on hysteresis behavior between DPNR and ENR latex foam indicated that ENR latex foam exhibits higher hysteresis loss ratio compared to DPNR latex foam.
Keywords: Natural rubber latex foam; Fabrication